Pengembangan Media Pembelajaran Berbasis Kuis Interaktif Baamboozle pada Mata Pelajaran IPAS Kelas V SD Negeri 060872 Medan - Rahma Sari Dewi; Lidia Simanihuruk; Nurhairani Nurhairan; Fahrur Rozi; Winara Winara (Jurnal Ilmiah Dikdaya, 2026)
The purpose of this study is to determine the validity of learning media, to determine the practicality of learning media and the effectiveness of learning media developed on human respiratory system materials. The type of research is research and development (R&D) using the ADDIE model which consists of 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. The results of validation by material experts on Baamboozle's interactive quiz-based learning media obtained a score of 92% with the criterion of "Very Feasible". The results of validation by media experts obtained a score of 95% with the criterion of "Very Feasible". The results of the media assessment by teachers obtained a score of 95% with the criterion of "Very Practical". Meanwhile, the results of the students' responses obtained a score of 88% with the criterion of "Very Practical". Based on the results of the implementation, it was found that there was an increase in student learning outcomes, where the average learning outcome in the pre-test was 35.75 while the average in the post-test was 85.5. Learning using Baamboozle's interactive quiz-based learning media in class V on human respiratory system material was effectively used. This is evident from the average N-Gain score of 78.33 percent in the category of "Highly Effective".